Imperceptible learners: Students' reasons for keeping webcams off and strategies to address students' challenges - Huma Farid; Tania A Siddiqui; Rashna H Sukhia; Sana Jalil Hasan; Ayesha Naveed; Lubna Pasha (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: "Should students keep their webcams on or off during synchronous online classes?" is an unanswered question with educators' opinions divided on this aspect. Along with educators' perspectives, it is also important to unfold students' perspectives on this question. The objectives of this study were to determine the routine and opinion of students' regarding webcam usage and identification of students' reasons for not using webcams during online learning. MATERIALS AND METHODS: A cross-sectional study was carried out at Margalla Institute of Health Sciences, Rawalpindi, Pakistan. Census was done for data collection by including all dental students (n = 180) enrolled at the institute attending synchronous online preclinical and clinical operative dentistry classes. Data collection was carried out using a self-administrated questionnaire. Descriptive analysis was used to describe survey item responses. Pair-wise differences between demographic categories (female vs. male, and preclinical vs. clinical) were analyzed using the Pearson Chi-Square test. Correlation of routine and opinion with students' reasons were done using Spearman correlation. Ordinal regression analysis was done to associate routine and opinion with reasons. The level of significance (P value) was set at 0.05. RESULTS: Out of 180 students, 141 submitted the survey form, with a response rate of 77.47%. The majority of the students (n = 117, 83%) used to keep their webcams off during online classes and were (n = 69, 48.9%) of the opinion that webcams should be kept off during online classes. The most common reasons for keeping the webcam off during online classes were "comfort" (n = 87, 61.7%) and "distractions" (n = 84, 59.6%). A statistically significant association of gender was obtained, with females more likely than males due to distraction, self-consciousness, and appearance (P = 0.000, 0.003, and 0.016, respectively). The odds of gender highly influenced routine use of cameras, and this was statistically significant (OR: 3.478, P = 0.011). Students tended to keep their webcam off when they were inattentative during online classes (OR; 3.743, P < 0.001). CONCLUSION: The majority of the students did not agree to keep the webcam on during online synchronous learning. The main reasons for students' reluctance to keep the webcam on were self-consciousness, surrounding consciousness, distractions, and technological issues. Students can be encouraged to turn the webcam on by framing strategies according to students' concerns.